4 - The Culture of Middle-level Academic Management at a Comprehensive South African University - Mavunga, George (Journal of Higher Education in Africa, 2022)
Using Critical Realism (CR), which emphasises the interplay of structure, culture, and agency, this conceptual article reflects on the culture of middle- level academic management at a comprehensive South African university which was the result of a merger of historically disparate institutions. It is important for the culture of this layer of management to be understood because it is at the nexus of senior management’s strategic initiatives and the concerns of staff members and students. The article thus recommends the implementation of practices which embed the corporatist concerns of senior-level management into those aspects of the culture of middle-level academic management which are a function of the structural contexts in which the middle level academic managers operate as well as the managers’ collective and individual agency. The result, the article envisages, could be an enhanced culture of middle-level academic management which makes for improved institutional governance in response to the multiple challenges being faced by the institution, such as the slow pace of transformation; increased student enrolments; student academic under-preparedness; the ever-present possibility of student protests; the demands of corporatism and the impact of the Fourth Industrial Revolution (4IR) on teaching and learning as well as unanswered questions around the relevance of some academic programmes.